Position Adherence in Patients Underwent Pars Plana Vitrectomy with Silicone Oil Tamponade - Gao S; Huang N; Huang W; Lian Y; Xiao H; Yao S (Patient Preference and Adherence, 2024)
Saiyu Gao,1– 3 Nanqi Huang,4 Wenmin Huang,5 Yu Lian,5 Huiming Xiao,5 Shuyu Yao5 1Department of Geriatrics, Xiangya Hospital, Central South University, Changsha, Hunan, People’s Republic of China; 2National Clinical Research Center for Geriatric Disorders, Xiangya Hospital, Central South University, Changsha, Hunan, People’s Republic of China; 3Teaching and Research Section of Clinical Nursing, Xiangya Hospital of Central South University, Changsha, Hunan, People’s Republic of China; 4Department of Gastroenterology, The Third Affiliated Hospital of Guangzhou Medical University, Guangzhou, People’s Republic of China; 5Ocular Emergency and Trauma Department, State Key Laboratory of Ophthalmology, Zhongshan Ophthalmic Center, Sun Yat-sen University, Guangdong Provincial Key Laboratory of Ophthalmology and Visual Science, Guangdong Provincial Clinical Research Center for Ocular Diseases, Guangzhou, People’s Republic of ChinaCorrespondence: Shuyu Yao, Email yaoshuyu@gzzoc.comIntroduction: Position adherence of patients with Pars Plana Vitrectomy with Silicone Oil Tamponade after discharge is of positive significance. However, patients undergoing a day surgery makes the quality of discharge teaching and readiness for hospital discharge is insufficient, which will influence their position adherence at home.Aim: This study aimed to find the correlation of discharge teaching, readiness for hospital discharge, and position adherence in patients who underwent PPV with silicone oil tamponade from the day ward.Methods: This was a cross-sectional survey. One hundred ninety-four patients with day surgery were recruited by convenient sampling from Zhongshan Ophthalmic Center, China. Data were collected using the quality of discharge teaching scale, readiness for hospital discharge scale, and position adherence scale.Results: Patients’ education level, residence, poor postoperative vision, ophthalmic surgery history, and quality of discharge teaching are the main factors of readiness for discharge. Only 41(21%) patients had good position adherence, and education level and readiness for discharge are the main factors of position adherence.Discussion: Discharge teaching improves patients’ knowledge and competence of self-care and helps patients prepare for the transition from hospital to home, and readiness for hospital discharge significantly influences position adherence after discharge and indirectly plays a vital role in postoperative vision recovery and surgical effect.Keywords: discharge teaching, readiness for hospital discharge, position adherence, pars plana vitrectomy with silicone oil tamponade